Estimativa da idade do polvo, Octopus insularis capturado com espinhel de potes no Ceará, relacionada com os estágios de maturação gonadal - Batista, Bruno Braulino (2011)
The growing interest in cephalopod fisheries due to overexploitation of the main fishing resources (teleosts and crustaceans). In Ceará, fishing for octopus Octopus insularis, started in 2004, as an alternative to the closed lobster season, but only in 2005 the fishery has become effectively trade. For the management of a fishery, growth and reproduction are the main factors to be studied, the main factors that affect growth are temperature and salinity. This study aimed to investigate qualitative and quantitatively morphometry to quantify the age, to validate the methodology, and the proportion of sexual maturity with morphometric variables (CM and Wt) and number of days. 20 specimens were sampled monthly, and their morphometric variables collected from the body and the upper beak, the validation of the quantification was done using the marker oxytetracycline (OTC), the quantification of age was performed by counting the number of increments of lateral wall the upper beak, the proportion by gonadal macroscopic characterization of the gonads. The growth of the octopus, Octopus insularis was influenced by temperature, in which the octopuses in the rainy season had higher values of dorsal mantle length and total weight. Moreover, the difference between the slopes (b) of the regressions for females showed that octopuses grow different between sexes and according to time of year (dry or wet). The marking of lines increase the sidewalls of the nozzles showed a profile of daily deposition, and thus the species has an extremely short life cycle of up to 6 months (180 days) and thus demonstrating that these animals are rapidly growing . Quantification of age on the sidewalls of the upper beak showed good correlation with the length of the dorsal mantle and crest length of the upper beak, but a weak correlation was obtained with the total weight. In this study, we used only octopuses sub-adults and adults, but still need to study the profile of deposition of rings in the side wall of the upper beak of paralarvas.